Pengaruh Pengalaman Magang, Minat Kerja, Dan Soft Skills Terhadap Kesiapan Kerja Mahasiswa Di Universitas Sarjanawiyata Tamansiswa - Halawa, Weall Cristal Hagani; Subiyanto, Didik; Purnamarini, Tri Ratna (Jayapangus Press, 2025)
This study aims to explore the influence of internship experience, job interest, and soft skills on students' job readiness. Students need to be well-prepared to face the challenges of the professional world. This research employs a descriptive quantitative approach, focusing on students from the Management Study Program at Sarjanawiyata Tamansiswa University, class of 2021. Data were collected through a questionnaire using a Likert scale to measure students' perceptions of internship experience, job interest, soft skills, and job readiness. The questionnaire was distributed to 72 students selected using purposive sampling, with the criteria of having completed an internship and being actively enrolled as students in the 2021 cohort of the Management Study Program. The total population in this study consists of 252 students. Various statistical analyses were conducted to analyze the data, including reliability and validity tests, t-tests, F-tests, and determination coefficient analysis. The results indicate that internship experience has a positive and significant impact on students' job readiness. The more work experience students have, the higher their readiness to enter the workforce. Additionally, job interest also has a positive and significant effect on job readiness, as a high level of motivation drives students to develop the necessary competencies. Soft skills likewise contribute significantly to job readiness, as these abilities help students adapt to changes in the workplace. Overall, this study concludes that internship experience, job interest, and soft skills simultaneously influence students' job readiness.